Reflections on the “Circle-breaking” Phenomenon of Dance Education in Colleges and Universities in the New Media Era - Yang, Wenjia (Journal of Educational Research and Policies, 2025)
Driven by new media, dance education in colleges and universities is undergoing a profound “circle breaking” change. This phenomenon is a result of multiple intertwining of social and cultural contexts, educational technology innovation and transformation of educational concepts, which not only contains opportunities but also brings controversies and challenges. This study combines the characteristics of the new media era, describes the multi-dimensional presentation of “circle breaking” in dance education in colleges and universities in the new media era, analyses dual driving force of this phenomenon and explores the strategies. It aims to provide theoretical references and practical paths for the innovative transformation of dance education in colleges and universities.